Soil crop systems and edaphic fauna diversity on the southern plateau of Santa Catarina - Brazil - Baretta, Dilmar; Santos, Julio Cesar Pires; Bertol, Ildegardis; Alves, Mauricio Vicente; Manfoi, Alex Fernando; Baretta, Carolina Riviera Duarte Maluche (Revista de Ciências Agroveterinárias, 2006)
This study aimed to evaluate the impact of different soil tillage and crop management systems on the edaphic fauna abundance and diversity. The work was carried out in Lages, Santa Catarina State, on a Haplumbrept soil type, from February to December of 2001. The following soil preparation systems were assessed: conventional tillage (CT); minimum cultivation (MC); and notillage (NT). Each soil preparation system was evaluated under crop rotation (cr/with corn, soybean, and wheat) and crop succession (cs/with soybean and wheat). An additional treatment of conventional tillage with no crop was also tested (NC). Fauna was sampled in February, April, June, October, and December of 2001, using six pitfall traps distributed randomly on each treatment plot. Abundance and diversity of the soil fauna were sensitive to both soil tillage and crop systems. NTcs and MCcs treatments showed the highest soil fauna diversity while the treatment NC showed the smallest one. Collembola, Acarina and Hymenoptera accounted for more than 90% of total organisms occurrence in all the evaluated systems. Cluster analysis based on fauna similarity revealed a first cluster made of CTcr, MCcr and NTcr. A second cluster consisted of CTcs and SC. Finally both MCcs and NTcs were isolated from the other studied systems.